Educational Leadership as a Response to the Contemporary Reality of the Global COVID – 19 Pandemic - Dorota Balcerzyk (Communications of International Proceedings, 2021)
The article presents reflections on educational leadership in contemporary reality. The publication critically analyzes the literature on educational leadership paradigms. It addresses the specificity of the role and social expectations placed on the teacher. The analysis of teacher competencies and their development direction, taking account of the COVID - 19 pandemic threats, was carried out. The considerations presented allowed for the conclusion that a teacher is the most fundamental link of educational leadership and, as an educational leader, builds potential, developmental opportunities, abilities to be effective in the new changing world. Educational leadership guarantees constancy and sustainability, responding to the challenges and complexity of the environment. The teacher as an educational leader is a buffer organizing educational situations to eliminate difficulties and threats. The analysis results indicate the directions of building educational leadership relations as modern leadership, which is a solution for passing through a period of uncertainty and change.
Keywords: Leadership; Educational Leadership; Competencies; Teacher’s Role